Enhanced through-thickness electrical conductivity and lightning strike damage response of interleaved vertically aligned short carbon fiber composites. (15th March 2023) - Kumar, Vipin; Lin, Wenhua; Wang, Yeqing; Spencer, Ryan; Saha, Subhabhrata; Park, Chanyeop; Yeole, Pritesh; Hmeidat, Nadim S.; Herring, Cliff; Rencheck, Mitchell L.; Pokkalla, Deepak Kumar; Hassen, Ahmed A.; et al.
Abstract: Through-thickness electrical conductivity of carbon fiber reinforced polymers (CFRPs) is a key characteristic that determines the severity of lighting strike-induced damage. Carbon Fibers (CFs) are inherently electrically conductive and therefore provide high conductivity in the direction of the fiber orientation. However, electrical conductivities through the thickness and orthogonal to the CF orientation in CFRPs are governed by the insulating polymer matrix present between CFs. In this work, through the thickness alignment of short CFs in between layers of CFRP laminates is demonstrated to improve the through-thickness electrical conductivity. Composites with interleaved vertically aligned short CF fibers (<150 μm) will be referred as V-fiber composites hereafter. The effect of the V-fiber on the lightning strike damage is evaluated against an artificial lightning strike of 100 kA (modified waveform A of SAE ARP-5412B standard). The improved through-thickness electrical conductivity of CFRP laminates (1.15 S/cm) through vertical alignment of short CFs was compared to reference CFRP laminates (0.13 S/cm) and was found to dissipate the artificial lightning strike current more efficiently. The surface damage after the artificial lightning strike in the V-fiber composites was reduced to 12.69 cm 2 compared to the reference CFRP surface damage of 57.67 cm 2, a 78% reduction. It was also demonstrated that Joule heat generated due to lightning strike on the composites was significantly less than the reference sample using infrared (IR) thermography. A high retention (up to 78%) of flexural properties (modulus and strength) was observed in V-fiber composites post lightning strike impact as compared to only 47% retention in the reference panel.